2000
DOI: 10.1385/bter:75:1-3:235
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Uranium Poisoning on Cultured Preimplantation Embryos

Abstract: The toxic effect of uranium in cultured preimplantation embryos of the mouse is presented. Embryos were obtained from hybrid females CBA x C57 BL following induction of superovulation and were incubated in M16 cultured medium. Two different experiments were performed. In one, embryos in a one-cell stage were placed in culture media with final concentrations of uranyl nitrate of 104 and 208 microg/mL during 120 h in the same dish. In the other experiment, embryos in a one-cell stage were placed in culture mediu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Uranium is also known to accumulate in areas of bone growth (Neuman et al, 1948;Rodrigues et al, 2013;Rowland and Farnham, 1969), where active calcification is occurring Durbin and Wrenn, 1975). Furthermore, ex-vivo studies using mouse preimplantation embryos (Kundt et al, 2000), and in vivo studies using the nonmammalian vertebrates Danio rerio and Xenopus laevis have shown that uranium exposure reduces embryo growth (Bourrachot et al, 2008;Mitchell et al, 2005). Taken together, the available studies provides evidence for a direct effect of uranium in developing animals.…”
Section: Discussionmentioning
confidence: 92%
“…Uranium is also known to accumulate in areas of bone growth (Neuman et al, 1948;Rodrigues et al, 2013;Rowland and Farnham, 1969), where active calcification is occurring Durbin and Wrenn, 1975). Furthermore, ex-vivo studies using mouse preimplantation embryos (Kundt et al, 2000), and in vivo studies using the nonmammalian vertebrates Danio rerio and Xenopus laevis have shown that uranium exposure reduces embryo growth (Bourrachot et al, 2008;Mitchell et al, 2005). Taken together, the available studies provides evidence for a direct effect of uranium in developing animals.…”
Section: Discussionmentioning
confidence: 92%
“…Intratesticular injection of enriched uranium compounds increased the incidence of cytogenic damage in developing mouse sperm (Hu and Zhu, 1990). In vitro studies showed that uranium is both cytotoxic and genotoxic to Chinese hamster ovary (CHO) cells (Lin et al, 1993) and reduces cell number in developing mouse embryos in culture (Kundt et al, 2000).…”
Section: Uranium and Enriched Uranium Compounds Early Experiments Bymentioning
confidence: 99%
“…Lin et al (1993) indicated that uranium can produce decreased viability, depressed cell cycle kinetics, and an increase in several genotoxic endpoints in CHO cells. Uranium, delivered as uranyl nitrate, delayed development of mouse embryos in culture and was associated with lower embryo cell numbers through the hatched blastocyst stage, suggesting that uranium exposure resulted in severe alterations in DNA synthesis (Kundt et al, 2000). Several other metals arrest cell division under certain conditions, including chromium (VI) (Zhang et al, 2001), iron (Philpott et al, 1998), nickel (II) (Shiao et al, 1998), lithium (Mao et al, 2001), and beryllium (Lehnert et al, 2001).…”
Section: Mechanisms Of Pathogenesismentioning
confidence: 99%
“…Studies of natural uranium compounds in rodents indicate that uranium is teratogenic and potentially toxic for the reproductive tissues (Domingo 2001;Arfsten et al 2001). There are a few studies available on male and female reproduction (Llobet et al 1991;Linares et al 2005;Arfsten et al 2005;Sanchez et al 2006) and in vivo or in vitro embryotoxicity (Domingo et al 1989;Kundt et al 2000); nevertheless, to our knowledge, there are no reports on oocytes with this contaminant at any dose.…”
Section: Introductionmentioning
confidence: 99%